THE EFFECT OF SCANNING METHOD ON THE STUDENTS’ READING COMPREHENSION AT SMP SWASTA IT IKHWANUL MUSLIMIN - Najmi, Farhan; Ramadhan, Achmad; Daulay, Sholihatul Hamidah (BRIGHT VISION Journal of Language and Education, 2025)
Reading is one of the subjects to get information and knowledge about everything readers need from the wrnitten form. Reading comprehension is the ability to drive meaning from written material. Readers are considered successful when they understand the meaning intended by the writer. Main purpose behind reading is to make connections between what you already know and what you need to know. Knowing why you are reading will greatly increase your chances of understanding the material. In the context of this study, scanning is seen as the most potential strategy to be applied for students’ reading comprehension. This research was conducted on March 2023/2024 academic year. The subject in this research is the students of eight grades at SMP Swasta IT Ikhwanul Muslimin located on Bandar Klippa, Percut Sei Tuan, and Deli serdang regency. This research used quantitative method. Experimental research method as a technique used to determine the impact of specific treatments. This study use experimental design with two classes they are an experimental class and control class. The research participants were eighth-grade students from SMP Swasta IT Ikhwanul Muslimin. There are two classes of eighth- grade students consist of 49 students. The result of Post-Test in experimental class showed significant effect with the pre-test and post-test in the experimental class whose pre-test score with a minimum of 32 and a maximum of 68 with a mean of 52 while in the post-test 64 minimum score, and a maximum score of 96 with a score of 82.31 as the mean score. The results prove that scanning method has a significant impact on Students' reading comprehension at SMP Swasta IT Ikhwanul Muslimin.